Analisis Sentimen Kesehatan Mental Menggunakan K-Nearest Neighbors Pada Sosial Media Twitter - Mahesworo Langgeng Wicaksono; Rusdah Rusdah; Diwi Apriana (Universitas Budi Luhur, 2022)
Mental health issues are still significant health problems in the modern world. Poor understanding, stigma, and low mental health awareness contribute to efforts to educate people about mental health. The issue of mental health is widely discussed on social media, one of which is Twitter. So it is necessary to analyze sentiment on mental health issues on Twitter. The dataset in this study uses community reviews on May 16, 2022, with the search word